Analysing the influence of trade, technology learning and policy on the employment prospects of wind and solar energy deployment: The EU case. (April 2020) - Ortega, Margarita; Río, Pablo del; Ruiz, Pablo; Nijs, Wouter; Politis, Savvas
Abstract: Job creation is arguably an important socioeconomic benefit of renewable energy deployment. In turn, this employment creation may be contingent upon the influence of some key factors, including technology learning, trade effects and policies and may affect different renewable energy technologies and activities of the renewable energy value chain in different ways. This paper estimates the gross employment stemming from the deployment of three renewable electricity technologies – photovoltaics (PV), wind on-shore and wind off-shore – up to 2050 for all Member States of the European Union. It uses a novel analytical methodology which is able to capture the influence of technology learning and internal and external trade. Additionally, it provides highly disaggregated results per activity in the supply chain (manufacturing, installation and O&M), year and country for different technology and policy scenarios. The results show that the employment created by those three technologies can be significant but considerable differences across technologies, activities and countries can be observed. In the analyzed period (2014–2050), most employment will be created in the PV sector, in the operation and maintenance activities and it will be highly geographically concentrated in a few countries. However, job creation will strongly depend on the scenarios and assumptions being made. In particular our findings suggest that the availability of carbon capture and storage will have a considerable influence on the number of jobs being created. In contrast, changes in other assumptions have limited effects on the results: a variable (vs. a constant) learning rate, more restrictive emissions targets by 2050 and higher PV costs. Highlights: Ex-ante calculation of the employment of wind and PV deployment in 2050 in the EU. Consideration of different policy scenarios, trade and technology learning effects. Total employment is expected to increase significantly in the period, driven by PV. Most jobs are created in the O&M and installation stages. Job creation is geographically concentrated in a few countries.